Introduction: social movements and forums in times of authoritarian capitalism. Issue 2 (17th February 2020) - Wallgren, Thomas; Pyakurel, Uddhab Pd.; Pardo, Catalina Revollo; Teivainen, Teivo
ABSTRACT: On all continents the enormity of the violence and danger of the times gives rise to multiple new practices of struggle and to conceptual innovations, which seek to serve justice, solidarity, and dignity for all. We explore the possibilities and different worlds intended in the main slogan of the World Social Forum 'Another world is possible'. During its early years the World Social Forum was characterized by a fair amount of optimism. We know now that most of the high hopes of the movements have not been adequately materialized. The rise of authoritarian leaders and the nexus between capitalism and populism emerging in different parts of the world has created a new context for the attempts to create democratic futures. This collection presents and interrogates a variety of diagnoses of the present and of new strategies for transformative change that are emerging out of the forum process.